Effective brain network analysis in unilateral and bilateral upper limb exercise training in subjects with stroke - Xu, Gongcheng; Huo, Congcong; Yin, Jiahui; Li, Wenhao; Xie, Hui; Li, Xiangyang; Li, Zengyong; Wang, Yonghui; Wang, Daifa (Medical physics (Lancaster), 2022)
Purpose Knowing the patterns of brain activation that occur and networks involved under different interventions is important for motor recovery in subjects with stroke. This study aimed to study the patterns of brain activation and networks in two interventions, affected upper limb side and bilateral exercise training, using concurrent functional near‐infrared spectroscopy (fNIRS) imaging. Methods Thirty‐two patients in the early subacute stage were randomly divided into two groups: unilateral and bilateral groups. The patients in the unilateral group underwent isokinetic muscle strength training on the affected upper limb side and patients in the bilateral group underwent bilateral upper limb training. Oxyhemoglobin and deoxyhemoglobin concentration changes (ΔHbO2 and ΔHbR, respectively) were recorded in the ipsilateral and contralateral prefrontal cortex (IPFC and CPFC, respectively) and ipsilateral and contralateral motor cortex (IMC and CMC, respectively) by fNIRS equipment in the resting state and training conditions. The phase information of a 0.01–0.08 Hz fNIRS signal was extracted by the wavelet transform method. Dynamic Bayesian inference was adopted to calculate the coupling strength and direction of effective connectivity. The network threshold was determined by surrogate signal method, the global (weighted clustering coefficient, global efficiency, and small‐worldness) and local (degree, betweenness centrality, and local efficiency) network metrics were calculated. The degree of cerebral lateralization was also compared between the two groups. Results The results of covariance analysis showed that, compared with bilateral training, the coupling effect of CMC → IMC was significantly enhanced (p = 0.03); also, the local efficiency of the IMC (p = 0.01), IPFC (p < 0.001), and CPFC (p = 0.006) and the hemispheric autonomy index of IPFC (p = 0.007) were significantly increased in unilateral training. In addition, there was a significant positive correlation between the coupling intensity of the inter‐hemispheric motor area and the shifted local efficiency. Conclusions The results indicated that unilateral upper limb training could more effectively promote the interaction and balance of bilateral motor hemispheres and help brain reorganization in the IMC and prefrontal cortex in stroke patients. The method provided in this study could be used to evaluate dynamic brain activation and network reorganization under different interventions, thus improving the strategy of rehabilitation intervention in a timely manner and resulting in better motor recovery.